Entomopathogens from agricultural soil and their pathogenicity against the potato leaf miner, Liriomyza huidobrensis (Diptera: Agromyzidae). Issue 8 (3rd August 2022) - Mugala, Thabu; Visser, Diedrich; Malan, Antoinette P.; Addison, Pia
ABSTRACT: The potato leaf miner, Liriomyza huidobrensis (Diptera: Agromyzidae), is an important economic pest of potatoes across the world, causing substantial damage in most potato-growing areas. The use of local entomopathogens for the control of insect pests has been widely encouraged, coupled with several environmental advantages being contrasted to the effects achieved using chemical pesticides. The current study surveyed potato field soil to determine the presence of entomopathogenic nematode (EPN) and entomopathogenic fungi (EPF) species in the Sandveld region of the Western Cape province. Susceptibility of L. huidobrensis larvae and pupae to the isolated pathogens and other locally sourced isolates was evaluated. The results of the survey indicated the presence of an unknown free-living bacteria feeding insect-associated nematode species of the genus Acrobeloides, the EPN Heterorhabditis zealandica and two EPF species, Metarhizium robertsii and M. majus. All L. huidobrensis pupal (45–57%) and larval stages (52–72%) of the potato leaf miner showed susceptibility to the EPN species tested. Laboratory bioassays showed that the pupal and larval stages was the most susceptible (>72% infection) to Heterorhabditis baujardi . Liriomyza huidobrensis pupal stage showed high pathogenicity to isolates of M. robertsii (10C). Overall, all isolates of M. robertsii showed pupal pathogenicity ranging between 80% and 91%. Metarhizium robertsii outperformed Beauveria bassiana as a biocontrol agent against L. huidobrensis pupae in the laboratory. Results from this study indicate the potential of biologicals as future biocontrol agents in an integrated pest management system for potato production.